Reducing Dietary Sodium to 1000 mg per Day Reduces Neurovascular Transduction Without Stimulating Sympathetic Outflow. Issue 3 (March 2019) - Babcock, Matthew C.; Robinson, Austin T.; Migdal, Kamila U.; Watso, Joseph C.; Wenner, Megan M.; Stocker, Sean D.; Farquhar, William B.
Abstract : The American Heart Association recommends no more than 1500 mg of sodium/day as ideal. Some cohort studies suggest low-sodium intake is associated with increased cardiovascular mortality. Extremely low-sodium diets (⩽500 mg/d) elicit activation of the renin-angiotensin-aldosterone system and stimulate sympathetic outflow. The effects of an American Heart Association–recommended diet on sympathetic regulation of the vasculature are unclear. Therefore, we assessed whether a 1000 mg/d diet alters sympathetic outflow and sympathetic vascular transduction compared with the more commonly recommended 2300 mg/d. We hypothesized that sodium reduction from 2300 to 1000 mg/d would not affect resting sympathetic outflow but would reduce sympathetic transduction in healthy young adults. Seventeen participants (age: 26±2 years, 9F/8M) completed 10-day 2300 and 1000 mg/d sodium diets in this randomized controlled feeding study (crossover). We measured resting renin activity, angiotensin II, aldosterone, blood pressure, muscle sympathetic nerve activity, and norepinephrine. We quantified beat-by-beat changes in mean arterial pressure and leg vascular conductance (femoral artery ultrasound) following spontaneous sympathetic bursts to assess sympathetic vascular transduction. Reducing sodium to 1000 mg/d increased renin activity, angiotensin II, and aldosterone ( P <0.01 for all) but did not alter mean arterial pressure (78±2 versus 77±2 mm Hg, P =0.56), muscle sympathetic nerve activity (13.9±1.3 versus 13.9±0.8 bursts/min, P =0.98), or plasma/urine norepinephrine. Sympathetic vascular transduction decreased ( P <0.01). These data suggest that reducing sodium from 2300 to 1000 mg/d stimulates the renin-angiotensin-aldosterone system, does not increase resting basal sympathetic outflow, and reduces sympathetic vascular transduction in normotensive adults. Abstract : Supplemental Digital Content is available in the text.